Enhancing Adolescent Awareness of Chronic Disease Through Community-Based Education and Health Assessment - Fitri Mailani; Tiurmaida Simandalahi; Hema Malini; Emil Huriani; Devia Putri Lenggogeni; Boby Febri Krisdianto; Leni Merdawati; Rahmi Mutia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Adolescents are increasingly vulnerable to chronic diseases such as hypertension, diabetes mellitus, and heart disease, largely due to unhealthy lifestyles and poor dietary habits. This community service initiative aimed to improve adolescents’ knowledge and awareness regarding chronic disease prevention. The program was implemented at SMAN 9 Padang, involving 58 students, and comprised health education through lectures and individual health assessments—including measurements of weight and height, and family medical history screening. Results indicated that 34.5% of students were classified as underweight based on their body mass index (BMI), while 20.7% were overweight. Identified risk behaviors included smoking (22.3%), physical inactivity (35.5%), and a family history of hypertension (43.1%). The educational intervention led to a significant improvement in students' knowledge, with the average score increasing from 6.74 (pre-test) to 7.82 (post-test) on a 10-point scale. This school-based education and health screening initiative effectively enhanced adolescent awareness of chronic disease prevention and underscored the importance of early interventions to foster healthier lifestyles among youth.